If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(15 + -35) + -1(7s + 1) = 60 Combine like terms: 15 + -35 = -20 -1(-20) + -1(7s + 1) = 60 Multiply -1 * -20 20 + -1(7s + 1) = 60 Reorder the terms: 20 + -1(1 + 7s) = 60 20 + (1 * -1 + 7s * -1) = 60 20 + (-1 + -7s) = 60 Combine like terms: 20 + -1 = 19 19 + -7s = 60 Solving 19 + -7s = 60 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -7s = 60 + -19 Combine like terms: 19 + -19 = 0 0 + -7s = 60 + -19 -7s = 60 + -19 Combine like terms: 60 + -19 = 41 -7s = 41 Divide each side by '-7'. s = -5.857142857 Simplifying s = -5.857142857
| b^2=20b | | 16+9w=7+27w | | -40000x^2+8820x+190000=0 | | 12x+-5y=2 | | x^2=512 | | q=r+st | | 4x^2y-6xy^2+5xy= | | h=2gh | | 3(3k+5)-11k+5+5= | | 7x=5x | | 9s-100= | | -2p+7=6-(7p+8) | | -7x=-8 | | 2x+4=-2x+1 | | -2p+7=5-(7p+8) | | 49x=33 | | 57-(5x+3)=5(x+2)+x | | w^2=6(w-2) | | a/5-4=-3 | | 2(4x-3)-8=4+2 | | 9-3w=-2+4w | | 52-(2x+7)=2(x+5)+5 | | 52-(2x+7)=2(x+5)+5solve | | 5x+3=3x-17 | | x^2+5x-915=0 | | 0.10x+.05(4-x)=.10(1) | | (3x-3)=16-(-7+x) | | 3(4-10y)=8(8y+16) | | 6k-3(2k-3)= | | -3(2s-6)-18=2(6s+7)-2 | | 27750+200x=312.50x | | 3(z-22)=36-3(z-2) |